The microenvironment in human myeloid malignancies: emerging concepts and therapeutic implications - Medyouf, Hind (Blood, 2017)
Similar to their healthy counterpart, malignant hematopoietic stem cells in myeloid malignancies, such as myeloproliferative neoplasms, myelodysplastic syndromes, and acute myeloid leukemia, reside in a highly complex and dynamic cellular microenvironment in the bone marrow. This environment provides key regulatory signals for and tightly controls cardinal features of hematopoietic stem cells (HSCs), including self-renewal, quiescence, differentiation, and migration. These features are essential to maintaining cellular homeostasis and blood regeneration throughout life. A large number of studies have extensively addressed the composition of the bone marrow niche in mouse models, as well as the cellular and molecular communication modalities at play under both normal and pathogenic situations. Although instrumental to interrogating the complex composition of the HSC niche and dissecting the niche remodeling processes that appear to actively contribute to leukemogenesis, these models may not fully recapitulate the human system due to immunophenotypic, architectural, and functional inter-species variability. This review summarizes several aspects related to the human hematopoietic niche: (1) its anatomical structure, composition, and function in normal hematopoiesis; (2) its alteration and functional relevance in the context of chronic and acute myeloid malignancies; (3) age-related niche changes and their suspected impact on hematopoiesis; (4) ongoing efforts to develop new models to study niche-leukemic cell interaction in human myeloid malignancies; and finally, (5) how the knowledge gained into leukemic stem cell (LSC) niche dependencies might be exploited to devise novel therapeutic strategies that aim at disrupting essential niche-LSC interactions or improve the regenerative ability of the disease-associated hematopoietic niche.